2015
DOI: 10.1039/c5lc00398a
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a microfluidic immunoassay capable of multiplexing parallel samples in microliter volumes

Abstract: Immunoassays are widely utilized due to their ability to quantify a vast assortment of biomolecules relevant to biological research and clinical diagnostics. Recently, immunoassay capabilities have been improved by the development of multiplex assays that simultaneously measure multiple analytes in a single sample. However, these assays are hindered by high costs of reagents and relatively large sample requirements. For example, in vitro screening systems currently dedicate individual wells to each time point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…We have shown that the driven transport of paramagnetic or diamagnetic colloidal particles above a two dimensional lattice is topologically protected by topological invariants of the modulation loops used to drive the transport [20,21]. Non-topological transport of particles in a dissipative environment is usually vulnerable because of a spreading of the driven motion with the distribution of properties of the classical particles [22][23][24][25][26][27][28] as well as due to the abundance of possible hydrodynamic instabilities [29,30] that limit the control over their motion. Topologically protected particle transport in contrast is robust against sufficiently small continuous modifications of the external modulation.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the driven transport of paramagnetic or diamagnetic colloidal particles above a two dimensional lattice is topologically protected by topological invariants of the modulation loops used to drive the transport [20,21]. Non-topological transport of particles in a dissipative environment is usually vulnerable because of a spreading of the driven motion with the distribution of properties of the classical particles [22][23][24][25][26][27][28] as well as due to the abundance of possible hydrodynamic instabilities [29,30] that limit the control over their motion. Topologically protected particle transport in contrast is robust against sufficiently small continuous modifications of the external modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Topological protection might be used to transport a broad distribution of particles without dispersion, despite their different properties. High precision multiparticle transport is an important ingredient in, for example, multifunctional lab-on-a-chip devices 10 11 .…”
mentioning
confidence: 99%
“…As improvements in technology occur over time, early vaccine assays are often re-designed and bridged to assays with higher throughput, multiplexed detection, reduction of sample volumes, and automation to support testing of large numbers of specimens for late-stage clinical trials. [28][29][30][31][32][33][34][35] Often, a variety of tests are evaluated early in the program and, based on the usefulness of the data, a down-selection occurs so that the most relevant few remain to support large Phase 3 clinical trials and licensure of the vaccine. 2,35,36 Accepted "gold standards" of immunoassays for use at the onset of an EID vaccine program are rare.…”
Section: Vaccine Clinical Assays Reference Reagents International Cmentioning
confidence: 99%